Ethinylestradiol and its effects on the macrophages in the prostate of adult and senile gerbils - Castro, Nayara F. C. [UNESP]; Falleiros-Junior, Luiz R. [UNESP]; Zucao, Mariele I. [UNESP]; Perez, Ana P. S.; Taboga, Sebastiao R. [UNESP]; Santos, Fernanda C. A.; Vilamaior, Patricia S. L. [UNESP] (Wiley-Blackwell, 2020)
Prenatal and neonatal exposure to estrogenic compounds, such as ethinylestradiol (EE), promotes a variety of developmental disorders, including malformations and alterations in the morphology of glands, such as the prostate gland. Therefore, the aim of this study was to evaluate the morphological effects of neonatal exposure to EE on prostatic tissue and on the identification and quantification of gerbil gland macrophages in adult and senile Mongolian gerbils. The animals were exposed to EE (10 mu g/kg/day) and to the vehicle, mineral oil (100 mu L) (control group) during the first 10 days of postnatal life (lactation period). Adult gerbils were euthanized at 120 days and senile gerbils at 12 months of age. Our findings permitted verification of the presence of areas with proliferative foci in the prostate glandular portions in the adult and senile animals exposed to EE. There was also an increase in macrophages in the prostate tissue of adult and senile gerbils; these cell types alter the stromal microenvironment and possibly modify the interactions between the epithelium and stroma. Neonatal exposure to EE changes the pattern of prostatic development, leading to alterations in the arrangement of cells, including macrophages, and may be related to the onset of proliferative disorders in the prostate of adult gerbils and during aging.
Keywords: animals; ethinylestradiol; gland; macrophage; neonatal; prostate